Molecular characterization of the rDNA-ITS sequence and a PCR diagnostic technique for Pileolaria terebinthi, the cause of pistachio rust - ALAEI, Hossein; MOHAMMADI, Amir Hossein; DEHGHANI, Ali (Phytopathologia Mediterranea, 2012)
Eleven samples of the most important pistachio rust (caused by Pileolaria terebinthi (DC.) Cast.,), which causes disease on Beneh (Pistacia atlantica Desf. subsp. mutica (Fisch. & Mey.) Rech. F) and Kasoor (Pistacia khinjuk Stocks.), were collected from herbarium specimens and pistachio fields at the Pistachio Research Institute in Rafsanjan, Iran. The complete sequences of ribosomal DNA internal transcribed spacers ITS1 and ITS2 (rDNA ITS) from the samples were determined and analysed. In general, very little rDNA ITS sequence variation was observed between rDNA ITS sequences of P. terebinthi samples. The length of the PCR fragments was 621 bp (for ITS1F-ITS4) and 1177 bp (for ITS1F-rust1), and consisted of 67 bp at the 3 ́ end of 18S rDNA, 93 bp of ITS1 region, 154 bp of 5.8S rDNA, 246 bp of the ITS2 region, 57 bp (for ITS1F-ITS4) and 613 bp (for ITS1F-rust1) at the 5 ́ end of the 28S rDNA. Restriction fragment length polymorphisms (RFLPs) of the rDNA-ITS region were used to identify Pileolaria terebinthi. Three strong bands of 105, 134 and 381 bp and five bands of 105, 134, 200, 301 and 437 bp are observed for the fragment of “ITS1F-ITS4” and “ITS1F-rust1”, respectively. A PCR-RFLP diagnostic technique provided effective identification of the species by a unique pattern with the specific restriction enzyme XapI (ApoI).